Pengaruh Kualitas Pelayanan, Citra Perusahaan, dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Di Lembaga Bimbingan Belajar Kumon Ahmad Yani Probolinggo - Raihan Wishal Nafi; Novita Prastyaningsih (Fakultas Ekonomi Universitas Panca Marga, 2019)
This research was conducted at the Institute of Tutoring Kumon Ahmad Yani Probolinggo with the objectives of the research to be achieved are (1) To know the significant effect of service quality, corporate image, and customer satisfaction on customer loyalty simultaneously in the Institute of Tutoring Kumon Ahmad Yani Probolinggo (2) To knowing the significant influence of service quality, corporate image, and customer satisfaction on customer loyalty partially in the Institute of Tutoring Kumon Ahmad Yani Probolinggo (3) To know among the variable quality of service, corporate image, and customer satisfaction that dominant influence on customer loyalty in the Institute of Tutoring Kumon Ahmad Yani Probolinggo. The Population in this research is all parent-student of Learning Guidance Institute Kumon Ahmad Yani Probolinggo which amounts to 395 people with the sample taken is counted 79 people with the criterion of parent-student who already use the service of Study Guidance Kumon Ahmad Yani Probolinggo minimum 1 year, with technique sampling is purposive sampling. The type of research used in this research is quantitative descriptive research with the associative approach, the variables used include service quality, corporate image, customer satisfaction, and customer loyalty. The data analysis method of this research is the quantitative descriptive method by using statistics in the form of instrument test, normality test, classical assumption test, multiple regression analysis, multiple correlation coefficient, determination coefficient, and hypothesis testing. The result of the research is shown of simultaneous hypothesis test F count equal to 25,623> F table 2,73 with significance value (Sig) 0.000b proves that service quality, customer satisfaction simultaneously affects customer loyalty. The result of partial hypothesis test t table = 1,992 and value of t arithmetic X1 = 2,668, X2 = 2,501, X3 = 4,728 with value of third Sig variable <0,05 proves that service quality, corporate image and customer satisfaction partially influence to customer loyalty. The result of the dominant hypothesis test shows that the X3 variable has t value greater than other independent variables. Keywords: Service Quality, Corporate Image, Customer Satisfaction, Customer Loyalty